Effects of ovariectomy on the inputs from the medial nucleus of the amygdala to the ventromedial nucleus of the hypothalamus in young adult rats - Gobbo, Denise Ribeiro; Pereira, Lais da Silva; Pacheco Ferreira, Jozelia Gomes; Castro Horta-Junior, Jose Anchieta de [UNESP]; Bittencourt, Jackson Cioni; Sa, Susana Isabel (Elsevier B.V., 2021)
During puberty, sexual hormones induce crucial changes in neural circuit organization, leading to significant sexual dimorphism in adult behaviours. The ventrolateral division of the ventromedial nucleus of the hypothalamus (VMHyl) is the major neural site controlling the receptive component of female sexual behaviour, which is dependent on ovarian hormones. The inputs to the VMHyl, originating from the medial nucleus of the amygdala (MeA), transmit essential information to trigger such behaviour. In this study, we investigated the projection pattern of the MeA to the VMHyl in ovariectomized rats at early puberty. Six-week-old SpragueDawley rats were ovariectomized (OVX) and, upon reaching 90 days of age, were subjected to iontophoretic injections of the neuronal anterograde tracer Phaseolus vulgaris leucoagglutinin into the MeA. Projections from the MeA to the VMHyl and to other structures included in the neural circuit responsible for female sexual behaviour were analysed in the Control and OVX groups. The results of the semi-quantitative analysis showed that penpubertal ovariectomy reduced the density of intra-amygdalar fibres. The stereological estimates, however, failed to find changes in the organization of the terminal fields of nerve fibres from the MeA to the VMHyl in the adult. The present data show that ovariectomized rats during the peripubertal phase did not undergo significant changes in MeA fibres reaching the VMHyl; however, they suggest a possible effect of ovariectomy on MeA connectivity under amygdalar subnuclei.
Keywords: Phaseolus vulgaris leucoagglutinin; Three-dimensional reconstruction; Female sexual behaviour; Ovarian hormones; Peri pubertal period; Neural circuits